2018
DOI: 10.1021/jacs.8b06180
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Binding Modes of N-Heterocyclic Carbenes on a Gold Surface

Abstract: Tuning the binding mode of N-heterocyclic carbenes on metal surfaces is crucial for the development of new functional materials. To understand the impact of alkyl side groups on the formation of NHC species at the Au(111) surface, we combined scanning tunneling microscopy, X-ray photoelectron spectroscopy, and density functional theory calculations. We reveal two significantly different binding modes depending on the alkyl chain length. In the case of a short alkyl substituent, an up-standing configuration wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(159 citation statements)
references
References 24 publications
10
142
0
7
Order By: Relevance
“…The adsorption energy was increased to −3.36 eV once the NHC was anchored on Au ad‐atom [Au‐ad/Au (111)] (Figure d). The enhanced adsorption energy is a result of stabilization of the bulky molecule on the defected surface . It should be noted that in both adsorption scenarios (with and without ad‐atom) the adsorption geometry was similar; the central NHC ring slightly tilted toward the surface, whereas the bulky NO 2 ‐decorated phenyl rings oriented parallel to the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption energy was increased to −3.36 eV once the NHC was anchored on Au ad‐atom [Au‐ad/Au (111)] (Figure d). The enhanced adsorption energy is a result of stabilization of the bulky molecule on the defected surface . It should be noted that in both adsorption scenarios (with and without ad‐atom) the adsorption geometry was similar; the central NHC ring slightly tilted toward the surface, whereas the bulky NO 2 ‐decorated phenyl rings oriented parallel to the surface.…”
Section: Resultsmentioning
confidence: 99%
“…30 Several groups have demonstrated that NHCs readily form robust self-assembled monolayer on coinage metal surface and function as a performance-enhancing modifier. [31][32][33][34][35][36] NHCs stabilized Au nanoparticles with excellent water-solubility, thermal stability, and chemical resistance to thiol exchange have also been reported. [37][38] Several coinage metal clusters stabilized by NHCs have been prepared as well.…”
Section: Introductionmentioning
confidence: 97%
“…Further analysis of the STM results revealed a reduction of the amount of carbene species at the surface to 18 % of the initial coverage after 125 hours, probably due to the formation of IMe‐Au‐IMe complexes, [6h] which might have a lower binding energy compared to the IMe‐Au species. However, the exact desorption process might involve a more complex pathway, which is not in the scope of the current study.…”
Section: Resultsmentioning
confidence: 99%